Operation labeling algorithm within Xamtanga sentences - Berhanu Asaye Agajie (Politeknik Negeri Bali, 2020)
The objective of this article was to look at the operation of the Labeling Algorithm within Xamtanga sentences. A descriptive research design was used to examine the research objective. The proposed sentences were gathered from Xamtanga college lecturers (3 males, 1 female) who teach the intended language. By expert sampling, eleven (11) sentences were chosen, prearranged, and portrayed. The method of data analysis working in this research was Labeling Algorithm XP, YP. Thus, results designated that simple sentences in Xamtanga have barely single Verbal heads. On the other hand, compound, complex, and compound-complex sentence structures have more than one verbal head. Regarding sentence appearances, Syntactic Object representations they enclose were dissimilar. Alternatively, every sentence types share Syntactic Object representations like Noun Phrase (NP), Verb Phrase (VP), Determiner Phrases (DP), Prepositional phrase (PP), Tense Phrase (TP), Adverbial Phrase (ADVP), and Adjectival Phrase (AP). Lastly, the study suggested that additional research on how XP, H, and X, Y employed to explain Xamtanga sentences.